2015
DOI: 10.1074/jbc.m114.626325
|View full text |Cite
|
Sign up to set email alerts
|

miR-28-3p Is a Cellular Restriction Factor That Inhibits Human T Cell Leukemia Virus, Type 1 (HTLV-1) Replication and Virus Infection

Abstract: Background: HTLV-1 has not been reported to be regulated by microRNA. Results: We discovered that cellular miR-28-3p reduces virus replication and infection. Conclusion: miR-28-3p may play an important role in limiting virus spreading. Significance: miR-28-3p may represent a therapeutic target for HTLV-1-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 52 publications
2
55
0
Order By: Relevance
“…Specifically, we found that levels of miR-28-3p were positively correlated with GRACE risk score and that miR-3135b was inversely correlated with GRACE risk score. MiR-28-3p, found in a variety of tissues, has been found to be associated with pulmonary embolism [39], colorectal cancer [40], and human T cell leukemia virus [41] but this is the first report to our knowledge showing a correlation of miR-28-3p with ACS risk. Further studies are needed to examine the role of miR-28-3p as an important biomarker in ACS and further mechanistic work to elucidate a potential therapeutic role for downregulating miR-28-3p levels in ACS.…”
Section: Discussionmentioning
confidence: 94%
“…Specifically, we found that levels of miR-28-3p were positively correlated with GRACE risk score and that miR-3135b was inversely correlated with GRACE risk score. MiR-28-3p, found in a variety of tissues, has been found to be associated with pulmonary embolism [39], colorectal cancer [40], and human T cell leukemia virus [41] but this is the first report to our knowledge showing a correlation of miR-28-3p with ACS risk. Further studies are needed to examine the role of miR-28-3p as an important biomarker in ACS and further mechanistic work to elucidate a potential therapeutic role for downregulating miR-28-3p levels in ACS.…”
Section: Discussionmentioning
confidence: 94%
“…Also, the location of a miRNA binding site in the 3’ UTR within 15 nucleotides from the stop codon can increase efficacy and repression of the target RNA [38]. However, not all naturally encoded viral miRNA interaction domains encode more than one miRNA binding site [17,18,41,42], and if there is more than one miRNA binding site, the sites may not be ideally located based on the aforementioned guidelines for cooperativity.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies show miRNA target influenza; vesicular stomatitis virus, human T-cell leukemia virus 1; human papillomavirus; and enterovirus 71, and they inhibit viral replication ( Fig. 7.3), which facilitates the clearance or potentiating viral latency of the pathogen (Bai and Nicot, 2015;Hen et al, 2014;Zheng et al, 2013). MiRNAs were also essential to show malaria transcripts translocation into the parasite (150).…”
Section: Micrornas In Emerging Diseasementioning
confidence: 99%
“…AA, Poly A tail; m7G, 7-methylguanosine cap; miRNAs, microRNA; ORF, open reading frame; RNA, ribonucleic acid. (Bai and Nicot, 2015). Although a few scientists agree on the direct interaction between miRNAs and viral transcripts, Bogerd et al (2014) argue that cellular miRNAs do not target viruses as global downregulation of host cell miRNAs (via DICER knockout) does not lead to the enhancement of 11 viruses in human embryonic kidney cell line 293T.…”
Section: Micrornas In Emerging Diseasementioning
confidence: 99%